2019
DOI: 10.1029/2019ja026832
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study on Multispacecraft Widespread Solar Energetic Particle Events During Solar Cycle 24

Abstract: We conduct a statistical study on the large three‐spacecraft widespread solar energetic particle (SEP) events. Longitudinal distributions of the peak intensities, onset delays, and relation between the SEP intensity, coronal mass ejection (CME) shock speed, width, and the kinetic energy of the CME have been investigated. We apply a Gaussian fit to obtain the SEP intensity I0 and distribution width σ and a forward‐modeling fit to determine the true shock speed and true CME width. We found a good correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…Correlation coefficients are <0.3 for the three energy channels. However, it is important to note that intensities in the >10 MeV energy channel are predominantly accelerated by the CME shock (Xie et al 2019). They are most significantly correlated with instantaneous CME velocities, but completely uncorrelated with intensities of X-ray flares.…”
Section: Associated Flares and Sep Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation coefficients are <0.3 for the three energy channels. However, it is important to note that intensities in the >10 MeV energy channel are predominantly accelerated by the CME shock (Xie et al 2019). They are most significantly correlated with instantaneous CME velocities, but completely uncorrelated with intensities of X-ray flares.…”
Section: Associated Flares and Sep Eventsmentioning
confidence: 99%
“…We can assume that the body of the CME is less significant than the CME front in SEP production. Very recently, Xie et al 2019 significantly improved previous considerations in two aspects. Using a three-dimensional CME reconstruction method and combined STEREO, SOHO, and Solar Dynamics Observatory (SDO) white light (WL) and extreme ultraviolet (EUV) observations as constraints, they were able to determine the true radial speed of the shock and CME angular widths.…”
Section: Introductionmentioning
confidence: 99%
“…These widespread SEP events have been extensively researched (e.g. Reames et al 1996;Wibberenz & Cane 2006;Lario et al 2006Lario et al , 2013Lario et al , 2016Dresing et al 2012Dresing et al , 2014Papaioannou et al 2014;Richardson et al 2014;Gómez-Herrero et al 2015;Paassilta et al 2018;Xie et al 2019) thanks to constellations of spacecraft widely distributed throughout the heliosphere, such as Helios 1, Helios 2, Ulysses, the SOlar and Heliographic Observatory (SOHO, Domingo et al 1995), the Solar TErrestrial RElations Observatory (STEREO, Kaiser et al 2008), and other planetary missions. The ever-changing configuration of the STEREO spacecraft is advantageous for the study of the longitudinal variations of SEP events near 1 au, together with, for instance, SOHO located at L1.…”
Section: Introductionmentioning
confidence: 99%
“…In the complex conditions (with or without twin-CME eruption) of SEP acceleration and transport, many factors could contribute to controlling the SEP peak intensity. Based on the general CME-SEP relationship, a large number of statistical studies have shown the correlations between CME properties (e.g., speed, angular width, or kinetic energy) vs. SEP I p (e.g., Gopalswamy et al 2004;Ding et al 2013;Kahler & Vourlidas 2005, 2014aRichardson et al 2014;Trottet et al 2015;Xie et al 2019;Kihara et al 2020;Zhuang et al 2020). Moreover, the relationship between the shock properties and SEPs was also analyzed (Kozarev et al 2015;Kouloumvakos et al 2019), as the shock strength is determined not only by the shock speed but also by the background (plasma density and magnetic fields).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the conditions described above, magnetic connectivity between the observing spacecraft and the SEP source region is one of the key factors in determining the in situ observed SEP level. The launch of the twin Solar TErrestrial RElations Observatory (STEREO, STA and STB hereafter;Kaiser et al 2008) extended the community's ability to study the longitudinal distribution of SEPs (e.g., Rouillard et al 2012;Lario et al 2013;Dresing et al 2014;Richardson et al 2014;Xie et al 2019). A Gaussian expression with a constant distribution width is typically applied to the observations to parametrize the longitudinal distribution of SEP intensities.…”
Section: Introductionmentioning
confidence: 99%